2021
DOI: 10.1029/2021gl093858
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Underpinning of Groundwater Use by Trees

Abstract: Transpiration mediates the transfer of water and energy between the land surface and the atmosphere (Fan et al., 2017;Good et al., 2015), impacting the regulation of climate and distribution of vegetation over land (Beerling & Berner, 2005). Trees play a particularly relevant role in water and energy transfer because they exhibit a wide range of maximum rooting depths (RD MAX ). This suggests that trees may be able to access groundwater that is not immediately available for evaporation. Root water uptake (RWU)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 76 publications
(139 reference statements)
1
15
0
Order By: Relevance
“…Both δ XYLEM datasets indicated that approximately 2/3 of hemlock‐transpired water was taken up by roots from the shallowest 30 cm of soils during the summer season. This finding is also in general agreement with observations of a reliance on shallow water uptake by conifers (Allen et al., 2019; Knighton et al., 2021). The lack of a significant correlation between K ROOT and DBH conflicts with empirical analysis of this data set (Li & Knighton, 2022).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Both δ XYLEM datasets indicated that approximately 2/3 of hemlock‐transpired water was taken up by roots from the shallowest 30 cm of soils during the summer season. This finding is also in general agreement with observations of a reliance on shallow water uptake by conifers (Allen et al., 2019; Knighton et al., 2021). The lack of a significant correlation between K ROOT and DBH conflicts with empirical analysis of this data set (Li & Knighton, 2022).…”
Section: Discussionsupporting
confidence: 91%
“…Though recent progress supports possible identification of individual species in mixed‐species stands (Mäyrä et al., 2021; Onishi & Ise, 2021; Schiefer et al., 2020), widely available vegetation index products (e.g., Normalized Difference Vegetation Index (NDVI), Vegetation Optical Depth (VOD)) may accurately support trait estimation for distinct species in mixed stands (Didan, 2015; Moesinger et al., 2020). Phylogenetic models can potentially predict traits from the underlying genetic relationships among plants; however, these methods are largely unvalidated (L. D. L. Anderegg et al., 2022; Knighton et al., 2021). New methods of estimating plant hydraulic traits could remove a significant barrier to progress in the study and simulation of soil‐water‐plant interactions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations